Effects of shrink fitting on iron losses of a permanent magnet synchronous motor with an amorphous core. Issue 9 (20th May 2022) - Zhu, Longfei; Fan, Bowen; Han, Xueyan; Tang, Renyuan
Abstract: In order to investigate the effects of shrink fitting on the amorphous core, a test device is designed and the magnetisation and specific iron loss characteristics of the amorphous core are measured. The specific iron loss of amorphous core increases since the eddy current loss in the stator yoke increases significantly. The iron losses of the permanent magnet synchronous motor with the amorphous stator core in consideration of the shrink fitting effects on the specific iron loss are analysed by FEA.